Pedagogical technologies for teaching environmental engineering in the online learning system of higher education institution (Educational Dimension, 2024)
The article outlines the pedagogical technologies for teaching environmental engineering in the online learning system of higher education institutions. There are proposed ways of developing educational technologies for teaching environmental engineering: active and collaborative learning, individualisation of training, use of video and audio materials, using electronic tools for evaluation of educational results, development of digital literacy, implementation of interactive online courses and professional communication and mentoring. There are presented the use of these technologies in the different aspects of environmental engineering, such as analysing water quality parameters,  soil quality assessment, studying waste management practices, and studying the integration of renewable energy into the practice through virtual labs, online tests, video lectures, and collaborative projects. The proposed pedagogical technologies for teaching environmental engineering in the online learning system of higher education institutions were tested in the educational process. The Student's t-test was used for statistical calculation of the obtained experimental data. At the end of the experiment, there is a statistically significant difference between the mean values of the experimental and control groups. It can be claimed that the use of pedagogical technologies for teaching environmental engineering in the online learning system of higher education institutions is perspective.
Keywords: professional training; environment engineering; online learning environment